Serum Amyloid Alpha Is Downregulated in Peripheral Tissues of Parkinson’s Disease Patients - Kurvits, Lille; Reimann, Ene; Kadastik-Eerme, Liis; Truu, Laura; Kingo, Külli; Erm, Triin; Kõks, Sulev; Taba, Pille; Planken, Anu (Frontiers in Neuroscience, 2019)
We report the changed levels of serum amyloid alpha, an immunologically active protein, in Parkinson’s disease (PD) patients’ peripheral tissues. We have previously shown that Saa-1 and -2 (serum amyloid alpha-1,-2, genes) were among the top downregulated genes in PD patients’ skin, using whole-genome RNA sequencing. In the current study, we characterized the gene and protein expression profiles of skin and blood samples from patients with confirmed PD diagnosis and age/sex matched controls. qRT-PCR analysis of PD skin demonstrated downregulation of Saa-1 and -2 genes in PD patients. However, the lowered amount of protein could not be visualized using immunohistochemistry, due to low quantity of SAA (Serum Amyloid Alpha, protein) in skin. Saa-1 and -2 expression levels in whole blood were below detection threshold based on RNA sequencing, however significantly lowered protein levels of SAA1/2 in PD patients’ serum were shown with ELISA, implying that SAA is secreted into the blood. These results show that SAA is differentially expressed in the peripheral tissues of PD patients.